2022
DOI: 10.3390/jof8101087
|View full text |Cite
|
Sign up to set email alerts
|

Management of Plant Beneficial Fungal Endophytes to Improve the Performance of Agroecological Practices

Abstract: By dint of the development of agroecological practices and organic farming, stakeholders are becoming more and more aware of the importance of soil life and banning a growing number of pesticide molecules, promoting the use of plant bio-stimulants. To justify and promote the use of microbes in agroecological practices and sustainable agriculture, a number of functions or services often are invoked: (i) soil health, (ii) plant growth promotion, (iii) biocontrol, (iv) nutrient acquiring, (v) soil carbon storage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Normally, BMs promote plant growth either by directly facilitating nutrient uptake (as biofertilizers) or by modulating (stimulating) plant hormone levels ( Russo et al., 2022 ). Improved nutrient uptake is frequent in the case of soil BMs that do not act as endophytes ( Nasslahsen et al., 2022 ), although it was reported that B. bassiana might enhance nutrient availability, particularly soluble phosphate ( Barra-Bucarei et al., 2019a ). Endophytization is more likely to activate plant hormones, especially those involved in plant growth and development ( Waadt et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, BMs promote plant growth either by directly facilitating nutrient uptake (as biofertilizers) or by modulating (stimulating) plant hormone levels ( Russo et al., 2022 ). Improved nutrient uptake is frequent in the case of soil BMs that do not act as endophytes ( Nasslahsen et al., 2022 ), although it was reported that B. bassiana might enhance nutrient availability, particularly soluble phosphate ( Barra-Bucarei et al., 2019a ). Endophytization is more likely to activate plant hormones, especially those involved in plant growth and development ( Waadt et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the dynamic changes in the endophytic bacteria community and metabolite content in plants were affected by many factors, including plant species [43], plant growth, and development stage [44]. Leaves are the environment for the survival of endophytes and the basis for the existence of metabolites.…”
Section: Leaf Nutrients With the Microbial Community And Differential...mentioning
confidence: 99%
“…The interactions between plants and their beneficial fungi, especially endosphere and rhizosphere microbes, are regarded as promising strategies to stimulate plant development in adverse environments such as saline lands [ 15 ] and heavy metal-contaminated lands [ 16 ]. Many plant-associated microorganisms can benefit plant health by positively influencing plant physiology, development, and environmental adaptation [ 17 , 18 ]. The mechanisms employed by plant-beneficial microorganisms to promote growth are involved in various ways.…”
Section: Introductionmentioning
confidence: 99%